Modeling Time in Computing - Furia, Carlo A; Mandrioli, Dino; Morzenti, Angelo; Rossi, Matteo (Monographs in theoretical computer science, 2012)
This book details the results of several decades of research on developing, analyzing, and applying time models to computing and engineering. Each chapter is supplemented with detailed bibliographic remarks and exercises of varying difficulty and scope.